Effect of phosphate solubilizing microorganisms and phosphorus chemical fertilizer on growth and phosphorus uptake of aerobic rice - Ilias, Nur Sakinah (2014)
In Malaysia, the cultivation of rice (Oryza sativa) is very important as it is the staple food of our country. A glass house study was conducted to determine the effect of phosphate solubilizing microorganisms and phosphorus chemical fertilizer on growth and phosphorus uptake of aerobic rice. The experimental treatments were arranged in Randomized Complete Block Design (RCBD) with four different bacterial treatments and three different rate of phosphorus fertilizer with 5 replications (4 × 3 × 5). The total treatments were 12 (T1 : uninoculated control + 30 kg of P₂O₅/ha; T2 : uninoculated control + 60 kg of P₂O₅/ha; T3 : uninoculated control + 120 kg of P₂O₅/ha; T4 : PSB16 + 30 kg of P₂O₅/ha; T5 : PSB16 + 60 kg of P₂O₅/ha; T6 : PSB16 + 120 kg of P₂O₅/ha; T7 : AM + 30 kg of P₂O₅/ha; T8 : AM + 60 kg of P₂O₅/ha; T9 : AM + 120 kg of P₂O₅/ha; T10 : PSB16 + AM + 30 kg of P₂O₅/ha; T11 : PSB16 + AM + 60 kg of P₂O₅/ha; T12 : PSB16 + AM + 120 kg of P₂O₅/ha). Pot experiment was conducted in the glasshouse at Ladang 10, UPM. Bacterial inoculums were applied to each of the respective pots which contain about 10 kg of soil. Plants were harvested 55 days after planting. The results showed that there was only a significant difference between bacterial treatments and rate of phosphorus fertilizer on fresh and dry weight of root. The uninoculated bacteria treatment with 60 kg of P₂O₅ / ha showed the most significant difference among the treatments for fresh and dry weight of root. However, there was no significant effect of other parameters between the interactions of the bacterial treatments and rate of phosphorus fertilizer.